Reductive Umpolung of Carbonyl Derivatives with Visible‐Light Photoredox Catalysis: Direct Access to Vicinal Diamines and Amino Alcohols via α‐Amino Radicals and Ketyl Radicals. Issue 23 (2nd May 2016) - Fava, Eleonora; Millet, Anthony; Nakajima, Masaki; Loescher, Sebastian; Rueping, Magnus
Abstract: Visible‐light‐mediated photoredox‐catalyzed aldimine–aniline and aldehyde–aniline couplings have been realized. The reductive single electron transfer (SET) umpolung of various carbonyl derivatives enabled the generation of intermediary ketyl and α‐amino radical anions, which were utilized for the synthesis of unsymmetrically substituted 1, 2‐diamines and amino alcohols. Abstract : Anilines can be coupled with aldimines or aldehydes in a visible‐light‐mediated photoredox‐catalyzed process. Reductive single electron transfer (SET) umpolung of the carbonyl derivatives leads to the generation of intermediary ketyl and α‐amino radical anions, which were used for the synthesis of unsymmetrically substituted 1, 2‐diamines and amino alcohols.